2021
DOI: 10.1002/ccr3.3896
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir administration to pregnant Japanese woman with chronic hepatitis B and hepatocellular carcinoma: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, species and dosage differences make it difficult to determine whether the toxicity observed in pregnant animals after exposure to ETV or ADV could be translated to humans administered with the drug’s therapeutic dosage. To date, there are only limited cases available in the scientific literature regarding the safety of ETV or ADV in unintended pregnant women ( Kakogawa et al, 2011 ; Gao et al, 2020 ; Kakiuchi et al, 2021 ). As far as we know, our study is the first disproportionality analysis utilizing real-world data from a large pharmacovigilance database to identify the association between the adiministration of ETV or ADV in pregnant women and the occurrence of AEDP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, species and dosage differences make it difficult to determine whether the toxicity observed in pregnant animals after exposure to ETV or ADV could be translated to humans administered with the drug’s therapeutic dosage. To date, there are only limited cases available in the scientific literature regarding the safety of ETV or ADV in unintended pregnant women ( Kakogawa et al, 2011 ; Gao et al, 2020 ; Kakiuchi et al, 2021 ). As far as we know, our study is the first disproportionality analysis utilizing real-world data from a large pharmacovigilance database to identify the association between the adiministration of ETV or ADV in pregnant women and the occurrence of AEDP.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA previously rated ETV and ADV as pregnancy category C agents, although that category classification is no longer applied due to oversimplified risk-benefit profile of the mother and fetus. Partly as a result, very few cases of patients treated with ETV or ADV during pregnancy have been reported in the literature ( Kakogawa et al, 2011 ; Gao et al, 2020 ; Kakiuchi et al, 2021 ). Limited reported cases may indicate that some women chose to continue administration of ETV or ADV for HBV treatment during pregnancy, with no evidence of increased incidence of birth defects in infants or higher risk of AEs for mothers ( Kakogawa et al, 2011 ; Yu et al, 2011 ; Gao et al, 2020 ; Kakiuchi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials have found that patients with hepatitis B cirrhosis may show liver fibrosis and increased expression levels of serum inflammatory factors during treatment, leaving them in a microinflammatory state for a long time and thus affecting the therapeutic effect [ 5 ]. Entecavir, adefovir dipivoxil, and lamivudine, with antibacterial and antivirus effects, are common and effective clinical drugs to treat liver cirrhosis [ 6 ]. Although entecavir has a good antiviral effect for newly diagnosed patients with hepatitis, they are easily affected by high variability of the virus.…”
Section: Introductionmentioning
confidence: 99%